VR-based avatar videos as an effective tool for process training in the context of digitalization? - Depenbusch, Sarah; Schaper, Niclas; Schürmann, Mirko; Schumacher, Jan-Philip (Frontiers in Computer Science, 2025)
In the context of digitalization, work processes are subject to constant change. To achieve overall process efficiency, it should be ensured that employees have a deep understanding of the work processes in which they are involved. Preliminary research has shown that the utilization of virtual reality (VR) environments, which visualize employees' workspaces and present VR avatars that demonstrate work process steps, can enhance employees' understanding of (future) work processes. However, implementing such virtual environments entails certain challenges, such as the necessity of training employees in the utilization of VR technology. Thus, the delivery of VR avatar simulations in a video format (VR-based avatar video) may present a flexible alternative solution. Focusing on related work, it can be assumed that VR-based avatar videos (VRA videos) help learners build a coherent mental model of their work processes by providing contextualized visual information that is close to real life. Furthermore, the visual design elements included in a VRA video (e.g., the VR avatar and virtual workspace) may increase employees' motivation to learn. Despite the potential benefits of VRA videos, critics may argue that these videos contain an excessive amount of visual detail, thus increasing learners' cognitive load. Due to these contradicting opinions, the present study investigates the potential advantages of a VRA video in enhancing employees' understanding of work processes compared to a schematically designed voice-over slides video (VOS video). Furthermore, the study compares the motivational impact of both videos. In an online experimental study, participants (N = 121) were randomly assigned to either the VRA or the VOS video group. One-way ANOVAs revealed that the VRA video group achieved significantly better transfer scores than the VOS video group. Results of the motivation questionnaires (based on the ARCS model) demonstrated that attention (ARCS-A), relevance (ARCS-R), and satisfaction (ARCS-S) were significantly higher in the VRA video group than in the VOS video group.